Determinan Harga Saham Perusahaan Makanan Minuman Tahun 2015-2018 - Mega Silviana; Anita Wijayanti; Purnama Siddi (Universitas Batanghari Jambi, 2020)
Stock prices are influenced by various factors. High stock prices can attract investors. research aims to find out whether the stock price is influenced by BVPS, TATO, FZ, EPS, PER. Study population of 14 food and beverage companies in 2015-2018. With the purposive sampling method, 11 companies were selected. Analysis with multiple linear regression. Stock prices are influenced by BVPS, FZ, EPS, PER, but TATO do not affect. It is hoped that this research can be taken into consideration for management and third parties in making decisions related to factors affecting stock prices.